A highly competitive system for CO methanation over an active metal-free fibrous silica mordenite via in-situ ESR and FTIR studies. (1st May 2020) - Hussain, I.; Jalil, A.A.; Fatah, N.A.A.; Hamid, M.Y.S.; Ibrahim, M.; Aziz, M.A.A.; Setiabudi, H.D.
Graphical abstract: Highlights: Fibrous silica mordenite (FSMOR) was synthesized by the microemulsion method. Porosity, oxygen vacancies and basicity were improved by new morphology of FSMOR. Oxygen vacancies performed as active sites to adsorb and activate the CO and H2 . FSMOR showed high CO methanation activity due to linearly adsorb CO. Fibrous morphology resisted coke deposition during the CO methanation reaction. Abstract: Catalytic methanation of carbon monoxide (CO) offers a sustainable and attractive way to produce the synthetic natural gas (SNG), which can be a substitute for fossil fuels (coal, petroleum and natural gas) towards a low carbon future. This study focuses on CO methanation over a modified mordenite (FSMOR), which was synthesized through a microemulsion method. The Physico-chemical properties of the synthesized FSMOR were examined by field emission scanning electron microscope (FESEM), X-ray diffraction (XRD), transmission electron microscopy (TEM), N2 adsorption-desorption isotherms, and electron spin resonance (ESR). The FSMOR showed a unique fibrous morphology, which has improved the CO conversion (73%), CH4 selectivity (71%) and rate of formation (0.0491 µmol-CH4 /m 2 s) remarkably due to enhancement in BET surface area, oxygen vacancies, and basicity. The FSMOR expressed high thermal stability and low carbon deposition compared to MOR, which was confirmed by thermogravimetric analysis (TGA), Raman and TEM observations. Besides, the in-situ ESR and FTIR observations proposed that the oxygen vacancies played a vital role to adsorb and activate the CO and H2 molecules via linear adsorbed CO* as intermediates, which dissociated into adsorbed C* to form methane by hydrogenation. This study may open up new opportunities for metal-free heterogeneous catalysis systems to enhance the catalytic CO methanation to produce SNG.